THE ANALYSIS OF EFL STUDENTS’ RESPONSES TO TEACHER FEEDBACK ON WRITING - Muhamad Taufik Hidayat (Institut Pendidikan Indonesia Garut, 2020)
Providing feedback is one teacher’s inevitable activity in the classroom. The feedback may occurs in different learning subjects, one of which is in writing course. In this subject, students need the feedback process more than other subject. However, not all students’ responded positively to this process of feedback. Relevant to the fact, this study was intended to find out the students’ responses to their teacher feedback especially in writing course. To that end, qualitative research analysis was used to explore and investigate this phenomena. Students enrolled in writing course were the main participants in this study. Interviews and observation were used as the primary instrument to collect the data needed. The result has revealed that students responses vary based on their own personal preferences. Some positively responded, some responded neutrally and the other responded negatively